2004
DOI: 10.1023/b:plan.0000036369.55253.dd
|View full text |Cite
|
Sign up to set email alerts
|

Members of a New Group of Chitinase-Like Genes are Expressed Preferentially in Cotton Cells with Secondary Walls

Abstract: Two homologous cotton (Gossypium hirsutum L.) genes, GhCTL1 and GhCTL2, encode members of a new group of chitinase-like proteins (called the GhCTL group) that includes other proteins from two cotton species, Arabidopsis, rice, and pea. Members of the GhCTL group are assigned to family GH19 glycoside hydrolases along with numerous authentic chitinases (http://afmb.cnrs-mrs.fr/CAZY/index.html), but the proteins have novel consensus sequences in two regions that are essential for chitinase activity and that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 72 publications
4
61
0
Order By: Relevance
“…Several lines of evidence, including coexpression, phenotypic resemblance, and reduced cellulose content, have suggested a functional link between the cell wall CESAs and the CTLs (Hauser et al, 1995;Zhong et al, 2002;Mouille et al, 2003;Zhang et al, 2004). Using live-cell imaging, we found that mutations in CTL1 reduced the velocities of the primary wall CSCs (Figure 1; see Supplemental Movie 1 online), indicative of reduced cellulose deposition in the mutant cell walls ( Figure 1D).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Several lines of evidence, including coexpression, phenotypic resemblance, and reduced cellulose content, have suggested a functional link between the cell wall CESAs and the CTLs (Hauser et al, 1995;Zhong et al, 2002;Mouille et al, 2003;Zhang et al, 2004). Using live-cell imaging, we found that mutations in CTL1 reduced the velocities of the primary wall CSCs (Figure 1; see Supplemental Movie 1 online), indicative of reduced cellulose deposition in the mutant cell walls ( Figure 1D).…”
Section: Discussionmentioning
confidence: 64%
“…However, CTL1 and CTL2 lack amino acids that are important for chitin binding and catalytic activity (Zhang et al, 2004).…”
Section: Ctl1 and Ctl2 Bind Glucan-containing Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The clustering of these genes with previously characterized chitinases from other species (Online Resource 6) and the presence or absence of a CBD suggests that Pg_GQ03206_D15.1 and Pg_GQ03803_J20.1 (cluster 1) are class IV chitinases; Pg_GQ0207_E09.1 (cluster 1) is a c l a s s V I I c h i t i n a s e ; P g G Q 0 1 8 3 _ A 0 6 . 2 a n d Pg_GQ03904_P01.1 (cluster 2) are class I chitinases; Pg_GQ03703_O09.1 and Pg_GQ03902_B01.1 (cluster 2) are class II chitinases; and Pg_GQ0046_J03.1 (cluster 3) is a class II chitinase or chitinase-like (CTL) sequence (sensu Zhang et al 2004;Sánchez-Rodríguez et al 2012).…”
Section: Classificationmentioning
confidence: 99%
“…Chitinases have been implicated in a variety of developmental processes like seed germination (Wu et al 2001), senescence (Hanfrey et al 1996), and morphogenesis (Zhang et al 2004), including somatic embryogenesis (Wiweger et al 2003;Johnsen et al 2005). There is increasing evidence that chitinases can mediate developmental processes through biosynthesis, assembly, and/or remodelling of various cell wall components Zhang et al 2004;Sánchez-Rodríguez et al 2012;Wu et al 2012).…”
Section: Introductionmentioning
confidence: 99%